PENGARUH EFISIENSI PAJAK DALAM PEMBENTUKAN STRUKTUR MODAL: STUDI KASUS PADA SEKTOR PERBANKAN - NINDYAWAN, BELLA PUTRIE; NELAZ, YOLANDA SAFITRI (Fakultas Ekonomi Universitas Islam Indragiri, 2024)
Tax efficiency is an important issue in financial industry, as it has potential to influence funding decisions through debt ratios. This study aims to analyze the effect of tax efficiency on capital structure in banking companies in Indonesia. This study uses secondary data from annual financial statements of banks listed on Indonesia Stock Exchange for 2020-2023 period by selecting sample of 23 companies that has eligibility criteria. The multiple linear regression method was applied to analyze relationship between tax efficiency ratio, Debt to Equity and Debt to Total Assets ratios, with profitability and company size as control variables. The results show that tax efficiency ratio has a significant positive influence on Debt to Asset and has a negative effect on Debt to Equity. This conclusion is important to understand the importance of effective tax management and formulate financing strategies by considering tax efficiency as a key factor in decision-making related to capital structure